The small farmer inclusion in the economic development of Colombia (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
Colombian rural development is the core of Chapter 1 of the Peace Agreement between the Colombian Government and the FARC. The negotiators of the Agreement, albeit from different perspectives, recognized the urgent need to promote the Colombian rural development to overcome its traditional backwardness and thus, handle better, economic and social conflicts in these rural areas. In this regard, the Government of President Santos has been developing «Colombia Sows», the public comprehensive policy to enhance agricultural production. However, it looks that it would not meet expectations. Moreover, there is still the implementation of several of the policies required to achieve rural development and the inclusion of small rural producers.
Keywords: agriculture; rural economic and social situation; small farmers; production scales; Colombian Peace Agreement; Colombia Siembra (Colombia Sows) public policy